The influence of personality type on the risk of driving - Maria Chrisnatalia; Dian Kemala Putri; Karmilasari; Stephanus Benedictus Bera Liwun (INSPIRA: Indonesian Journal of Psychological Research, 2023)
Accidents are often caused by the driver himself, other people, or even the circumstances while driving. Even emotions influence behavior while driving. Individual factors relate to personality type. This research aims to determine the influence of agreeableness and neuroticism personality types on driving risks mediated by driving safety attitudes. The methods used in this research are experiments and surveys. The experimental tool used in this research is a driving simulator with the help of Urban Driving software. The experimental group was treated with a traffic volume and pedestrian density of 75%, and the control group was treated with a traffic volume of 50%. The measurement instruments used in this study consisted of a measure of risky driving behavior, a measure of aggressive driving behavior, a measure of agreeableness and neuroticism from the Big Five Scale, and attitudes towards safe driving. Thirty participants in this study were divided into two groups, namely the experimental and the control groups, with 15 participants. Based on the regression results of each group. The regression results show an influence of agreeableness and neuroticism mediated by driving safety attitudes on driving risks in the experimental and control groups; however, both groups have indirect impacts. These results prove that personality type greatly influences driving risk, mediated by driving safety attitudes.